Respuesta :
a) See free-body diagram in attachment
b) [tex]F_x=0, F_y=\frac{2akqQ}{(a^2+x^2)^{\frac{3}{2}}}[/tex]
c) [tex]F=\frac{2kqQ}{a^2}[/tex]
Explanation:
a)
The free-body diagram of the situation can be found in attachment.
We have:
- The charge of +q is located at y = a
- The charge of -q is located at y = -a
- The charge -Q is located at x = a
We observe that:
- The force exerted by charge +q on charge -Q is attractive, since the two charges have opposite sign, so it points to the north-west direction
- The force exerted by charge -q on charge -Q is repulsive, since the two charges have same sign, so it points to the north-east direction
So, the net force points north.
b)
We start by evaluating the situation on the x-direction first.
We observe that:
- The two charges +q and -q have same magnitude
- Also, they are located at exactly same distance from charge -Q
This means that the x-components of the force that each charge exerts on -Q are equal, but opposite in direction: therefore, they cancel each other, so the net force on the x-direction is zero:
[tex]F_x = 0[/tex]
Instead, we observe that the y-components of the force that each charge exerts on -Q are both upward, therefore they add together.
The distance between charge +q and charge -Q is:
[tex]r=\sqrt{a^2+x^2}[/tex]
where x is the location of the charge -Q.
The force between any of the two charges q, -q and charge -Q is given by (magnitude):
[tex]F=\frac{kqQ}{r^2}=\frac{kqQ}{a^2+x^2}[/tex]
However, we are only interested in the y-component of the force, which is given by
[tex]F_y = F cos \theta[/tex]
where [tex]\theta[/tex] is the angle between [tex]F_y[/tex] and [tex]F[/tex]. By using trigonometry,
[tex]cos \theta=\frac{a}{r}=\frac{a}{\sqrt{a^2+x^2}}[/tex]
So, substituting into the equation for [tex]F_y[/tex], we find
[tex]F_y = \frac{kqQ}{a^2+x^2}\cdot \frac{a}{\sqrt{a^2+x^2}}=\frac{akqQ}{(a^2+x^2)^{\frac{3}{2}}}[/tex]
However, the net force is the sum of the forces due to the 2 charges, so
[tex]F_y=\frac{2akqQ}{(a^2+x^2)^{\frac{3}{2}}}[/tex]
c)
Here we want to find the net force on the charge -Q when this is located at the origin, so when
x = 0
We already said that the net force on the x-direction is always zero, so
[tex]F_x=0[/tex]
Instead the net force on the y-direction is given by
[tex]F_y=\frac{2akqQ}{(a^2+x^2)^{\frac{3}{2}}}[/tex]
Therefore, by substituting x = 0, we find:
[tex]F_y=\frac{2akqQ}{(a^2+0^2)^{\frac{3}{2}}}=\frac{2akqQ}{a^3}=\frac{2kqQ}{a^2}[/tex]
And the net force is in the upward direction, towards charge +q.
![Ver imagen skyluke89](https://us-static.z-dn.net/files/dfe/e7dfc9a8bead9ec758e07cd49d7b1545.jpg)